Racial Resentment, Old‐Fashioned Racism, and the Vote Choice of Southern and Nonsouthern Whites in the 2012 U.S. Presidential Election*. (30th June 2015) - Knuckey, Jonathan; Kim, Myunghee
Abstract : Objective: The effects of racial attitudes on the vote choice of whites in the 2012 U.S. presidential election are examined, with a specific focus on the simultaneous effects of both racial resentment and old‐fashioned racial prejudice. Methods: Data are taken from the 2012 American National Election Study (ANES). Models of vote choice are estimated separately for southern and nonsouthern whites. Results: Findings show that racial resentment alone affected the vote choice of southern whites, but among nonsouthern whites both racial resentment and old‐fashioned racism exerted independent effects on vote choice. Furthermore, it was among independents that the effects of racial attitudes were most visible. Conclusions: Overall, it is estimated that racial attitudes cost Obama support among white voters, and likely made his victories in a number of swing states a lot closer than they would have been absent the effects of racial attitudes. Consistent with prior literature, findings also demonstrate that the election of the first African‐American president has primed old‐fashioned racial prejudice.